The Influence of Family Economic Education on Students’ Economic Behavior with Economic Literacy as a Mediating Variable - Ariani, Silvia Dwi Putri; Prakoso, Albrian Fiky (Perspektif Pendidikan dan Keguruan, 2024)
The research aims to determine the Influence of family economic education on the economic behavior of students at Muhammadiyah High School 10 GKB Gresik with economic literacy as a mediating variable. The type of research used is correlational research with a quantitative approach. A total of 118 class X students at SMA Muhammadiyah GKB Gresik were the samples in this research. Data was obtained from the results of questionnaires filled out by students. The data analysis technique used is SEM-PLS approach via WarpPLS 8 software. The research results show that directly, family economic education has a significant and positive effect on economic literacy, economic literacy has a significant and positive effect on economic behavior, and family economic education have a significant and positive effect on economic behavior. Other findings show that indirectly, family economic education has a significant and positive effect on economic behavior through economic literacy.